FEATURES OF THE COURSE OF ATYPICAL AND TYPICAL COMMUNITY-ACQUIRED PNEUMONIA IN CHILDREN - Boynazarov A. A.; Juraev I. K. (Web of Journals Publishing, 2025)
Despite significant progress in studying acute respiratory diseases in children, the incidence of pneumonia in childhood remains high, and diagnostic and therapeutic errors persist. To improve the current situation, practical guidelines on pneumonia in children have been published. However, specialists involved in developing these guidelines note the insufficient evidence base for many provisions and emphasize the need for further research. Most existing studies focus on severe cases of community-acquired pneumonia (CAP) and their complications. However, mild and moderate forms of CAP, which prevail in outpatient practice, pose equally serious challenges for researchers.